The Role of Database Management in the Accreditation of Study Programs at State Islamic Higher Education Institutions - Ikhwan Aulia Fatahillah; Dedah Jubaedah; Yana Sutiana (Westscience Press, 2024)
This study aims to analyze the management of databases at State Islamic Higher Education Institutions (PTKIN) in supporting the accreditation of study programs. The research adopts a descriptive qualitative approach, employing data collection methods such as interviews, observations, and documentation. Data were obtained from several PTKIN institutions in the Java region, including UIN Syarif Hidayatullah Jakarta, UIN Sultan Maulana Hasanuddin, and IAIN Pekalongan. The findings reveal that database management plays a crucial role in enhancing the accreditation scores of study programs by providing valid and relevant data. Strategic policies, such as strengthening human resources, implementing independent academic information systems, and conducting accreditation simulations by Quality Assurance Institutions, have proven effective in preparing study programs for assessment by the National Accreditation Board for Higher Education (BAN-PT). The study also highlights challenges, such as limited human resources and inconsistencies in reporting data, which can be addressed through technological innovations and continuous training. This research underscores the importance of integrated database management in supporting the quality of higher education at PTKIN.